Poly (β amino esters) copolymers: Novel potential vectors for delivery of genes and related therapeutics - Iqbal, Sajid; Zhao, Zhongxi (International journal of pharmaceutics, 2022)
[Display omitted] •Bio-functionalizations of materials is the subject of recent publications.•Developments in poly(β-amino esters) copolymers are critically discussed.•Ideas and directions of future research are proposed. The unique properties of polymers have performed an essential contribution to the drug delivery system by providing an outstanding platform for the delivery of macromolecules and genes. However, the block copolymers have been the subject of many recently published works whose results have demonstrated excellent performance in drug targeting. Poly(β-amino esters) (PβAEs) copolymers are the synthetic cationic polymers that are tailored by chemically joining PβAEs with other additives to demonstrate extraordinary efficiency in designing pre-defined and pre-programmed nanostructures, site-specific delivery, andovercoming the distinct cellular barriers. Different compositional and structural libraries could be generated by combinatorial chemistry and by the addition of various novel functional additives that fulfill the multiple requirements of targeted delivery. These intriguing attributes allow PβAE-copolymers to have customized therapeutic functions such as excellent encapsulation capacity, high stability, and stimuli-responsive release. Here, we give an overview of PβAE copolymers-based formulations along with focusing on most notable improvements such as structural modifications, bio-conjugations, and stimuli-responsive approaches, for safe and effective nucleic acids delivery.